Anthracene Fluorescence Quenching by a Tetrakis (Ketocarboxamide) Cavitand - Tibor Zoltan Janosi; Jouko Korppi-Tommola; Zsolt Csok; Laszlo Kollar; Pasi Myllyperkio; Janos Erostyak (Journal of Spectroscopy)
Quenching of both fluorescence lifetime and fluorescence intensity of anthracene was investigated in the presence of a newly derived tetrakis (ketocarboxamide) cavitand at various concentrations. Time-correlated single photon counting method was applied for the lifetime measurements. A clear correlation between the fluorescence lifetime of anthracene as a function of cavitand concentration in dimethylformamide solution was observed. The bimolecular collisional quenching constant was derived from the decrease of lifetime. Fluorescence intensity was measured in the emission wavelength region around 400 nm as a result of excitation at 280 nm. Effective quenching was observed in the presence of the cavitand. The obtained Stern-Volmer plot displayed upward curvature. The results did not follow even extended Stern-Volmer behavior, often used to describe deviations from static bimolecular quenching. To explain our results we adopted the Smoluchowski model and obtained a reasonable estimate for the molecular radius of the cavitand in solution.